2013
DOI: 10.1530/edm-13-0026
|View full text |Cite
|
Sign up to set email alerts
|

Pasireotide therapy in a rare and unusual case of plurihormonal pituitary macroadenoma

Abstract: SummaryWe report the use of pasireotide in a rare and unusual case of pituitary macroadenoma co-secreting GH, prolactin and ACTH. A 62-year-old Caucasian man presented with impotence. Clinically, he appeared acromegalic and subsequent investigations confirmed GH excess and hyperprolactinaemia. Magnetic resonance imaging (MRI) of pituitary revealed a large pituitary macroadenoma. He underwent trans-sphenoidal surgery and histology confirmed an adenoma with immunohistochemistry positive for ACTH, GH and prolacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 14 publications
(17 reference statements)
0
8
0
Order By: Relevance
“…These unusual combinations have been scarcely documented, and most publications have been on isolated cases or double PitNETs. Moreover, the typification of these tumors has been based on the IHC study of pituitary-specific hormones [28][29][30][31][32]. Only Kageyama et al [33] have described the IHC co-expression of NEUROD1, Tpit, and Pit-1 in a silent PitNET with positivity for ACTH and PRL.…”
Section: Discussionmentioning
confidence: 99%
“…These unusual combinations have been scarcely documented, and most publications have been on isolated cases or double PitNETs. Moreover, the typification of these tumors has been based on the IHC study of pituitary-specific hormones [28][29][30][31][32]. Only Kageyama et al [33] have described the IHC co-expression of NEUROD1, Tpit, and Pit-1 in a silent PitNET with positivity for ACTH and PRL.…”
Section: Discussionmentioning
confidence: 99%
“…Instead in this case a large (19 × 12 mm) lesion that seems to include all the pituitary with pituitary stalk widening, no clearly visible neurohypophysis bright spot and hypointense in both T1 and T2 is found with homogenous contrast uptake. This might suggest either corticotroph hyperplasia (although evidence for CRH oversecretion is lacking as noted), silent corticotroph macroadenomas (but there is clear analytical evidence for hypercortisolism) or mixed type corticotroph adenomas (but no evidence for other hormone secretion is found) [26][27][28]30]. Most interestingly is the pituitary stalk widening; this finding has been reported in relation to granulomatous or immune-mediated pituitary diseases in regard with hypopituitary states [15,16].…”
Section: Discussionmentioning
confidence: 91%
“…Despite a standardized clinical diagnostic and treatment approach [22][23][24], CD may be difficult to diagnose and to treat; and several uncommon variants are recognized like cyclic CD [25], intermediate lobe corticotroph adenomas [26], mixed corticotroph adenomas [27], silent corticotroph macroadenomas [28] and even the exceedingly rare corticotroph carcinoma [29]. Also apparent CD because of CRH hypersecretion, either a hypothalamic tumor or a peripheral neuroendocrine tumor [30], and the classic Nelson' syndrome [31] after bilateral adrenalectomy must be considered.…”
Section: Introductionmentioning
confidence: 99%
“…It also suggests the superior efficacy of pasireotide-LAR compared to a first-generation somatostatin analog, octreotide LAR, for the treatment of patients with acromegaly. Rajendran et al reported the use of pasireotide in a rare and unusual case of pituitary macroadenoma co-secreting GH, prolactin, and ACTH ( 10 ). In that case, the GH and IGF-1 levels improved significantly, but intermittent hypercortisolemia persisted.…”
Section: Discussionmentioning
confidence: 99%